Study the incidence, management and outcome of primary postpartum hemorrhage in a tertiary care hospital - Albina, Ayat; Zargar, Owais-ul-umer; Ashraf, Nashrah; Hak, Jyoti (International Journal of Research in Medical Sciences, 2022)
Background. Postpartum hemorrhage (PPH) is a major cause of serious maternal morbidity and mortality worldwide. To avoid the same, it is essential to find out avoidable factors and to reduce their consequences. So, the present study is taken to see the incidence, management and outcome of primary PPH in a tertiary care centre. Objective of current study was to study the incidence, management and outcome of primary PPH in a tertiary care hospital. Methods: This observational cross-sectional study was conducted in a tertiary care hospital over a period of one year. A total of 200 patients developing primary PPH after delivery were divided into two groups-Group A: Patients with primary atonic PPH and Group B: Patients with traumatic PPH. Results: The incidence of primary PPH in our study came out to be 8.3%. Most of the cases were in the age group of 26 -30 years. 84% of the patients belonged to rural areas. 72.5% of patients had hemoglobin levels below 9g%. The main cause of PPH in our study was uterine atony with an incidence of 73% followed by traumatic PPH in 24% cases. Cesarean sections constitute about 55% cases whereas spontaneous vaginal delivery constitutes 45% cases. Primary PPH was noted in 60% cases that underwent induction of labor followed by 28.9% having augmented labor and 11.1% had spontaneous onset of labor. Conclusions: Every pregnancy should culminate in a healthy mother and healthy baby and for that we should make sure that every woman should have access to top quality essential and emergency obstetric services to cut back maternal mortality. Finally, the surest prophylaxis of PPH is that the correct management of all stages of labor should be done.